SOCIO SCIENCE-TEACHING ON MADURA BULL RACING CONTEXT: FINDING CORRELATION BETWEEN NUMERACY LITERACY AND SCIENCE CONCEPTUAL UNDERSTANDING - Mochammad Yasir; Dwiyanti, Lusiana (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
The Madura bull racing as the local wisdom of Madura can be studied scientifically to train students in numeracy literacy and understanding concepts. Numerical literacy is important for students because it includes basic skills for obtaining new information. Numerical literacy is not only needed in mathematics, but is also needed to learn concepts in science subjects. The purpose of this study was to determine the relationship between numeracy literacy skills and students' understanding of science concepts towards the concept of motion and force in socio-science teaching in the Madura bull racing context. Data analysis used Spearman's rank correlation test. The results showed a significance value of 0.000 <0.05 with a correlation coefficient of 0.528, which means that there is a positive relationship with moderate closeness between numeracy literacy skills and understanding of the science concept of motion and force socio-science teaching in the Madura bull racing context with a determination coefficient of 0.278. The conclusion of this study is that the correlation of numeracy skills on students' understanding of science concepts regarding motion and force socio-science teaching in the Madura bull racing context is 27.88% and 72.12% is influenced by other factors, such as multi-representational skills, HOTs, etc. This research has implications for improving science learning designs using the context of the local wisdom of Madura bull racing in training science conceptual understanding and numeracy literacy skills.